2023
DOI: 10.1002/tqem.22131
|View full text |Cite
|
Sign up to set email alerts
|

Review of green technologies for the removal of microplastics from diverse environmental sources

S. Karthick Raja Namasivayam,
G. P. Avinash

Abstract: Microplastics are the basic particles (1 µm–1 mm), derived from degradation of polymers with maximum molecular weight via various sources. They occur in a variety of shapes and sizes, in the form of domains, particles, and fibers. Release of Microplastics in the ecosystem, due to deterioration of macroplastics are now being considered as major toxic pollutants. Accumulation of microplastics in the diverse ecosystems is known to cause severe health and ecological effects. Since it is mandatory to take steps tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…[23] Studies have shown that nanomaterials could be effectively applied for the adsorption of microplastics from marine environment. [24,25] Pourabadeh et al [26] used iron nanoparticles for the removal of reactive red 2 from aqueous solution. Shojaei et al [27] studied NaX nanozeolites for the removal of auramine-O and malachite green dyes from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Studies have shown that nanomaterials could be effectively applied for the adsorption of microplastics from marine environment. [24,25] Pourabadeh et al [26] used iron nanoparticles for the removal of reactive red 2 from aqueous solution. Shojaei et al [27] studied NaX nanozeolites for the removal of auramine-O and malachite green dyes from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, chitosan derived nanocomposite was used for the removal of disperse red 60 dye which is found in industrial effluent [23] . Studies have shown that nanomaterials could be effectively applied for the adsorption of microplastics from marine environment [24,25] . Pourabadeh et al [26] .…”
Section: Introductionmentioning
confidence: 99%